2000
DOI: 10.1080/713654932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age of release from light or food restriction on age at sexual maturity and egg production of laying pullets

Abstract: 1. Lohmann Brown pullets, in one trial, and Hyline Brown pullets in another, were reared from day 2 on short daylengths, and from week 8 in trial 1 (week 16 in trial 2) on food restriction. These restrictions were lifted at various times during the rearing period as a means of determining the relative importance of the day length and food restriction stimuli on the attainment of sexual maturity and subsequent laying performance. 2. A total of 2304 pullets were used in each trial. The birds were reared in light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Islam (2001) partially supported the present findings. The present findings, "body weight had no effect on egg weight" is supported by Sarker (2004) and Gous et al (2000). They found the increased egg weight with the increase of age of the bird.…”
supporting
confidence: 78%
“…Islam (2001) partially supported the present findings. The present findings, "body weight had no effect on egg weight" is supported by Sarker (2004) and Gous et al (2000). They found the increased egg weight with the increase of age of the bird.…”
supporting
confidence: 78%
“…The fact that the E60:P40, E40:P60 and EPFC treatments delayed days to first egg and the E60:P40 and E40:P60 treatments decreased body weight at first egg indicates that the pullets were not maintained on a feed programme providing all known required nutrients for growth and sexual development 4, 25, 28. Nevertheless, daily nutrient intakes of control, E60:P40 and EPFC birds were not significantly different (Table 4).…”
Section: Resultsmentioning
confidence: 97%
“…Many factors, e.g. manipulation of time of access to some nutrients,1, 2 quantitative3–5 or qualitative6, 7 feed restriction and choice feeding8–10 in the starter, grower and/or developer phases, have been reported to affect the growth curve, early egg weight and sexual maturity of pullets and consequently egg production. Therefore favourable genetic characteristics can only be achieved when the bird is provided with all its nutritional requirements 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed an usual trend that egg weight increased with the advancement of age. Gous et al (2000) found that egg weight increased with an increase in bird's age. Luykx (1994) observed larger egg from older hens.…”
Section: Standard Body Weight Achieved Body Weightmentioning
confidence: 99%